Learning Styles: An Overview - Amita Sood; Jyoti Sarin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Learning styles aim to know variations in individuals’ learning. As per most of the theories, humans may be classified in line with their‘style’of learning. The term “learning styles” speaks to the understanding that each student learns uniquely. Learning is a vital experience for individuals of all ages. Based on Howard Gardner’s Theory of Multiple Intelligences, there are eight varieties of learning styles that everybody falls into which include visual, aural, verbal, physical, logical, social, solitary and naturalistic learning. Learning style inventories are designed to assist respondents verify learning style they have. These inventories usually take the form of a questionnaire that focuses on how folks prefer to learn. Learning style inventories are based on the thought that individuals have completely different strengths and preferences when it involves learning. Learning style inventories remain a preferred classroom tool despite the actual fact that research has found very little proof that matching a student’s learning preferences to instructional methods produces better educational outcomes. These are a few popular types of learning style inventories such as Kolb’s Learning Style Inventory (LSI), Fleming’s VARK Learning Style Questionnaire, Jackson’s Learning Styles Profiler (LSP), Learning Style Quizzes.In short, it is important to remember that there are a number of learning styles and learning style inventories. Each learning style has its own advantages and disadvantages. Knowing your learning style is not meant to limit you, instead to expand you – by helping you to learn, understand, work and live more efficiently.